Origin of the Late Paleozoic metamorphic rocks in East Johor, Peninsular Malaysia - Sugeng Sapto Surjono; Shafeea Leman (Journal of Applied Geology, 2015)
Low grade metamorphic rocks including slate, phyllite, metasandstone with subordinate schist and quartzite are widely distributed in the East Johor, Peninsular Malaysia. Regionally, this rock unit is extended northward up to northern Terengganu area. The protolith of this rocks unit were deposited in shallow marine depositional environment that subsequently metamorphosed during Carboniferous time. The very thick argillaceous and arenaceous rocks more than 5000 metres were produced by fast rate accommodation spaces due to global sea level rise during Early to Late Carboniferous against with high fine-grained sediment supply. Tectonic setting, basin formation and sedimentation processes were controlled by rifting of Indochina-East Malaya continental block from Gondwanaland during Devonian to Late Carboniferous. This rifting formed basins within a passive margin tectonic setting along the western margin of Indochina-East Malaya continental block.Keywords: Metamorphic rocks, shallow marine, Carboniferous, passive margin